Representasi Sensualitas Wanita Pada Iklan Televisi “Segar Sari Susu Soda” Versi Julia Perez - Putri, Alifia Ananda (ISI Press Institut Seni Indonesia Surakarta, 2022)
Advertising as a promotional medium contains the ideology of persuasion. This research is motivated by the existence of a television advertisement for Segar Sari Susu Soda, a version of Julia Perez, which represents the exploitation of female sensuality. The research approach uses descriptive qualitative methods, which are carried out with the viewpoint of the theory of female sensuality in mass media (television) advertisements based on existing case studies. The aim is to analyze product advertisement impressions that contain elements of female sensuality by using Charles Sanders Peirce's theory and John Fiske's semiotic analysis theory to explore both the social and linguistic meanings visualized in these advertisements, both verbally and nonverbally. The results of this study indicate that the sensuality presented in the advertisement for Segar Sari Susu Soda's version of Julia Perez is a form of emotional conflict in the form of a mask of sensuality that is modified to become an element being sold, and if left unchecked will damage the character of sexuality in a socio-cultural perspective and damage religious and ethical values.